2023
DOI: 10.1002/ajb2.16215
|View full text |Cite
|
Sign up to set email alerts
|

Epiphytic bryophyte and lichen transplant niches along an elevational gradient in Pacific Northwest coniferous forests

Abstract: Premise of the studyThere is a lack of knowledge about the ability of individual species to grow successfully outside of their realized niche. The present study aims to investigate two epiphytic bryophyte and two epiphytic lichen species in their fundamental and realized niches in the Pacific Northwest coniferous forest at low, mid and high elevations.MethodsTwo lowland epiphytic bryophyte species (Frullania nisquallensis, Neckera douglasii) and one lowland epiphytic lichen species (Usnea longissima) were tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Previous studies have revealed the significant impact of ecological niches on altitude gradients on the abundance and richness of tree epiphytes [17] . Furthermore, there are distinct differences in the ecological niche of bryophytes across various altitude gradients, enabling them to survive in diverse environments [20] . Gaining insights into the ecological requirements and relationships of dominant bryophyte species along altitudinal gradients during resource utilization is crucial for the effective management and restoration of urban ecosystems.…”
Section: Ecological Niche and Interspecific Relationship Of Dominant ...mentioning
confidence: 99%
“…Previous studies have revealed the significant impact of ecological niches on altitude gradients on the abundance and richness of tree epiphytes [17] . Furthermore, there are distinct differences in the ecological niche of bryophytes across various altitude gradients, enabling them to survive in diverse environments [20] . Gaining insights into the ecological requirements and relationships of dominant bryophyte species along altitudinal gradients during resource utilization is crucial for the effective management and restoration of urban ecosystems.…”
Section: Ecological Niche and Interspecific Relationship Of Dominant ...mentioning
confidence: 99%